Transforming clinical practice in just one year: lessons from external cephalic version success - Maisa Manasar-Dyrbus; Bohdan Seifert; Agnieszka Drosdzol-Cop; Rafal Stojko; Jakub Staniczek (Ginekologia Polska)
OBJECTIVES: This study aimed to assess the safety and feasibility of implementing an external cephalic version (ECV) with routinely offered regional anesthesia and its impact on the cesarean section (CS) rate at a single large center in Poland. MATERIAL AND METHODS: A retrospective analysis was conducted on 110 pregnant women with non-cephalic fetal presentations who were offered an ECV procedure at term between October 2023 and November 2024. Patients were offered regional anesthesia regularly. The endpoints studied were the success rates of ECV, pain levels in the VAS (Visual Analogue Scale) score and subsequent delivery methods. A univariable regression model was employed to identify factors influencing ECV success. RESULTS: Of the 110 pregnant patients fulfilling the criteria for ECV, 56 underwent a total of 61 ECV attempts. Of those, 39 attempts (63.9%) were successful, resulting in 30 vaginal deliveries. Once administered, regional anesthesia significantly reduced procedural pain (VAS 3 [2–4] vs 0 [0–1] points, p < 0.001). A logistic regression model identified maternal BMI as a significant factor influencing ECV success (OR = 1.257, p = 0.018). Of the 61 attempts of ECV, two resulted in urgent cesarean section. ECV implementation resulted in a 2.12% reduction in the overall CS rate at the institution. Further reductions—up to nearly 4% — could be achieved if all eligible patients consented to the procedure. CONCLUSIONS: This study demonstrates that ECV, especially with regional anesthesia, is a feasible and effective strategy for reducing cesarean section rates and can be easily implemented into routine clinical practice. Widespread adoption of ECV could significantly decrease CS rates, improving perinatal care in Poland.